Temporal response of post-activation performance enhancement induced by a plyometric conditioning activity - Barreto, Marcos Vinicius Casais; Telles, Juliana Ferreira da Silva; de Castro, Marcela Rodrigues; Mendes, Thiago Teixeira; Rodrigues, Caio Portela; de Freitas, Victor Hugo (Frontiers in Sports and Active Living, 2023)
Introduction To better understand the post-activation performance enhancement (PAPE) effect promoted by a plyometric conditioning activity (CA), the aim of this study was to investigate the temporal response of PAPE after a plyometric CA. Methods Fourteen healthy and active adults visited the laboratory 3 times, with an interval of 7 days between each visit. On the first day they were familiarized with the countermovement jump (CMJ) test and plyometric CA. In the second and third visits, participants performed either plyometric CA or control (remaining seated) in a crossover design. The CMJ test was performed pre and 1-, 3-, 6-, and 9-min post the plyometric CA or control. The comparisons were performed using the repeated measure two-factor ANOVA and Bonferroni adjustment (significance level adopted P ≤ 0.05). Results Time (P < 0.01), condition (P < 0.01), and interaction (P < 0.01) effects were reported for CMJ comparisons. For the control condition, CMJ increased at 3 min compared to pre (P = 0.03) and at 3 min compared to 1 min (P = 0.03). For the plyometric CA, CMJ increased at 1- (P < 0.01), 3- (P < 0.01), and 6-min (P = 0.02) compared to pre. For condition comparisons, CMJ was different at 1- (P < 0.01), 3- (P < 0.01), 6- (P < 0.01), and 9-min (P = 0.02). The Effect size of the comparisons of all moments compared to pre was null (d < 0.20) for control and small (d < 0.50) for plyometric CA. Discussion It is possible to conclude that the plyometric CA promoted a PAPE effect for up to 9-min. Strength and conditioning coaches and practitioners may consider multiple sets of plyometric CA to produce immediate enhancement of power in the lower limbs.